2010
DOI: 10.1007/s00228-010-0890-6
|View full text |Cite
|
Sign up to set email alerts
|

The local vasoconstriction of infant’s skin following instillation of mydriatic eye drops

Abstract: The risks of percutaneous toxicity must always be considered in children, especially in premature neonates, in whom the epidermal permeability barrier is frequently incompetent. Application of smaller drop size or wiping of overflowed drop from the skin may be useful to decrease the risk of systemic side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The vasoconstriction periorbital has been reported previously, mainly in relation to the characteristics of the skin of the premature neonate, which are the most susceptible population 3 . However in this report, one of the reported cases is a term neonate, who in theory presents a lower risk, for he possess a less immature skin.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The vasoconstriction periorbital has been reported previously, mainly in relation to the characteristics of the skin of the premature neonate, which are the most susceptible population 3 . However in this report, one of the reported cases is a term neonate, who in theory presents a lower risk, for he possess a less immature skin.…”
Section: Discussionmentioning
confidence: 88%
“…It is clear that the group of infants, especially premature infants due to cutaneous characteristics, are the population at greatest risk for local and systemic complications, but we believe that there must be other associated factors in this population. This is due to the cases of Alpay et al 3 , who reported a similar event of vasoconstriction in a term neonate, which was not associated with hydrocephalus, but also did not clarify which factor could trigger it.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Systemic absorption of these drugs occurs primarily via nasal mucosa and conjunctiva, nasolacrimal duct, oropharynx, digestive system, and skin. 2,3 The toxicity is dose-related. 2 Early recognition of systemic toxicity after eye drop instillation is important.…”
Section: Discussionmentioning
confidence: 99%